Gender Diversity in the Executive Board : Progress Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper ;, 2020)
Executive Directors underscore the importance of promoting gender diversity at the IMF's Executive Board and the Offices of Executive Directors (OEDs). The Executive Board recognizes that a diversity of views contributes to stronger decision making and is committed to ongoing efforts to improve the gender profile of the Board and Offices of the Executive Directors. The Fund's membership has also indicated that it places importance on this issue; the International Monetary and Financial Committee (IMFC) has consistently drawn attention in its communiques to the importance of enhancing the gender diversity of the Executive Board.